Estimation of the resilient modulus for granular materials of Costa Rica - Múnera Miranda, Juan Carlos (2025)
The resilient modulus is a measure of the ability of a material to store or absorb energy without experiencing permanent deformation. This is determined by triaxial tests of repeated load and is an important parameter in the analysis and design of flexible pavements. With its value it is possible to predict the mechanical response of the pavement as stresses, deformations and deflections. However, obtaining it is expensive for the equipment involved and not all material laboratories have the test. Because of this, pavement designers use correlations to approximate a resilient modulus value, which generally differs considerably from that obtained with the test. The following research aims to estimate a universal model of a resilient modulus for granular materials that considers variables related to stress states and the basic characteristics of the materials. For this, a linear regression model was generated using ordinary least squares with data from at least 13 different granular materials. The model was validated by statistical indicators obtaining an acceptable goodness of fit.